Respiratory cancer in a cohort of nickel sinter plant workers. Issue 4 (November 1981) - Chovil, A; Sutherland, R B; Halliday, M
Abstract : A study was undertaken of a cohort of nickel refinery workers from a sinter plant that operated from 1948 to 1962. A complete follow-up of the 495 workers has been carried out by searching death records and other measures. Incidence cases known to the Workmen's Compensation Board of Ontario have been included. Fifty-four cases of lung cancer and eight of sinus cancer (including two in men who subsequently developed primary lung cancer) were located. The risk of lung and sinus cancer was much higher in the earlier days of operation of the plant, with an increase rate of over 40% for those employed in the first year of operation. The dose-response relationship has been examined by regressions of standardised morality ratios (SMR) and standardised incidence ratios (SIR). The SIR suggests that the risk doubled at levels of exposure of 12 months (six months in the earlier years).